Orlando Shooting not due Islam - Akhmetova, Elmira (2016)
Humanity is horrified by the tragic mass shooting, which took the lives of 49 people and wounded another 53 at the Pulse nightclub in Orlando, Florida, on June 12. It is considered to be the deadliest mass shooting by a single gunman in the United States’ history and the deadliest incident of violence against Lesbian, Gay, Bisexual & Transgender (LGBT) people.